After constructivism - Taylor, B (2011)
This thesis examines the legacy and consequences of Constructivism in art, from the early days of the Russian avant-garde to recent times and today. The Introduction explains how the concept of faktura, first theorised around 1912 by David Burliuk and others, came to designate the material qualities rather than the subject-matter of art. Chapter 1: Towards A Constructive Ideal, traces the progress of faktura in the reliefs of V.Tatlin from 1913. The ancestry of faktura in the Eastern icon tradition is emphasised, where a close relation between sight and touch already suggested a new type of encounter between the viewer and the object of art. The chapter further examines the importance of faktura to Suprematism, and examines A.Rodchenko’s appeal to line as a rational element of construction and as a weapon against ‘composition’ in art. Chapter 2: Time and the Viewer presents evidence of the importance to artists in the period 1940-70 of the real-time encounter between viewer and the art-object, first in American and British ‘Constructionism’, and then in the Minimal art of Judd, Morris and others. The chapter ends with a discussion of temporality in relation to abstract paintings of Rothko and de Kooning. Chapter 3: Irregular Curves: Science and ‘The Organic’ reprises the minority Constructivism of Mikhail Matyushin and Pyotr Miturich that claimed organic structures were superior to technicist ones. Evidence is presented that the rectilinear grid was always subject to challenge, initially in the art of Emma Kunz, Jean Arp and other pre-war modernists but latterly among those for whom ‘field’ and ‘curvature’ became relevant formats after 1945. Particularly with the development of computing from the 1970s, new geometries based on iteration and scale-invariancy assumed major relevance to constructed art. Chapter 4: Constructivism Now presents evidence of the application of Constructivist principles in recent art, initially in Dan Flavin’s ‘monuments’ to Tatlin and others and subsequently in so-called Neo-Geo and Op art of the 1970s and 1980s. From that period on, albeit often in a register of irony and ‘serious play’, faktura in a Constructivist sense continued, and continues today, to define the relation between viewer and object of art.